(untitled) (Journal of Health Sciences, 2022)
Introduction: With the advent of the COVID-19 pandemic, people’s dietary habits have changed, so the importance of additional supplementation has become a current topic. The aim of this study is to analyze the attitude of female respondents toward dietary supplementation before and during the COVID-19 pandemic.Methods: The research is a cross-sectional study conducted in two different time periods. The sample consisted of two female subsamples who purchased immunity preparations from Verdant Pharmacy before the pandemic (n = 81) and during the pandemic (n = 120). Female respondents in both subsamples were: Of the same age, in the same health condition, residing in the same area (municipality), users of a local pharmacy located near the health center. The research instrument was a non-standardized questionnaire “Assessment of attitudes towards nutritional supplementation,” which consisted of nine questions.Results: During the pandemic COVID-19, the attitude toward the use of preparations to strengthen immunity differs by 7% compared to the pre-pandemic check. The attitude toward the use of preparations to strengthen immunity throughout the year increased by 32.3% (53.3%) during the pandemic, and the attitude toward the choice of preparations to strengthen immunity changed by 13% during the pandemic COVID-19 based on own experience and by 17% based on the recommendation of the pharmacist.Conclusion: The pandemic COVID-19 has contributed to a change in female respondents’ attitudes toward nutritional supplementation to strengthen the immune system during a pandemic. With the help of the media, public health recommendations, and people’s fear of disease, the COVID-19 pandemic led to a change in respondents’ attitudes compared to the pre-pandemic period.